All-solid battery

The all-solid-state battery optimizes conductive additive distribution to balance conductivity and capacity by using carbon nanotubes with specific particle size peaks, addressing the challenges of heat resistance and capacity limitations in existing designs.

JP2024174497APending Publication Date: 2024-12-17TAIYO YUDEN KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023092352
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-05
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing all-solid-state batteries face challenges in achieving good battery operation while balancing the ratio of conductive additives that contribute to capacity, as using small particle sizes may not withstand heat during sintering, and large particle sizes require excessive amounts, leading to insufficient capacity.

Method used

The battery design includes a specific distribution of conductive additives with two peaks in particle size ranging from 5 nm to 130 nm, where the slope between peaks is 0.7 or less, and a frequency of 5% or more, using carbon materials like carbon nanotubes to ensure effective electron conduction and thermal stability.

Benefits of technology

This configuration achieves good battery characteristics by maintaining a low ratio of non-contributing conductive additives, ensuring sufficient conductivity and capacity without excessive material usage, thereby enhancing overall battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024174497000001_ABST
    Figure 2024174497000001_ABST
Patent Text Reader

Abstract

To provide an all-solid battery that can achieve good battery operation while keeping the ratio of conductive additives that do not contribute to capacity low.SOLUTION: An all-solid battery includes a solid electrolyte layer and electrode layers provided on both main surfaces of the solid electrolyte layer and containing an electrode active material and a conductive additive, and in a frequency distribution of particle diameters of the conductive additive in a cross section of the electrode layer, the two largest peaks, a first peak and a second peak, appear in a range of 5 nm or more and 130 nm or less, and in a cumulative distribution of the particle diameters, a point appears between the first peak and the second peak where the slope is 0.7 or less (% / nm).SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an all-solid-state battery. [Background technology]

[0002] All-solid-state batteries using oxide-based solid electrolytes are expected to be a technology that can provide safe secondary batteries that do not suffer from concerns about fire and toxic gas emissions, which are associated with organic electrolytes and sulfide-based solid electrolytes (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2021-034202 [Patent Document 2] International Publication No. 2014 / 042083 Summary of the Invention [Problem to be solved by the invention]

[0004] When a conductive assistant with a small particle size is used in the electrode layer, the electron conduction to each electrode active material is good, and good battery operation can be achieved. However, if the particle size is too small, the conductive assistant may not be able to withstand the heat during sintering. When a conductive assistant with a large particle size is used, the electron conductivity of the entire electrode layer is high, and good battery characteristics can be obtained. However, if the particle size is too large, the proportion of conductive assistant required to form an electron conduction path for each electrode active material is high, and high capacity may not be achieved.

[0005] The present invention has been made in consideration of the above problems, and has an object to provide an all-solid-state battery that can achieve good battery operation while keeping the ratio of a conductive assistant that does not contribute to capacity low. [Means for solving the problem]

[0006] The all-solid-state battery according to the present invention comprises a solid electrolyte layer, and an electrode layer provided on both main surfaces of the solid electrolyte layer and containing an electrode active material and a conductive additive, wherein in a frequency distribution of particle diameters of the conductive additive in a cross section of the electrode layer, the two largest peaks, a first peak and a second peak, appear in a range of 5 nm or more and 130 nm or less, and in a cumulative distribution of the particle diameters, a point appears between the first peak and the second peak where the slope is 0.7 (% / nm) or less.

[0007] In the all-solid-state battery, the first peak and the second peak in the frequency distribution may have a frequency of 5% or more.

[0008] In the all-solid-state battery, a difference between a particle size of the first peak and a particle size of the second peak may be 20 nm or more.

[0009] In the above all-solid-state battery, the area ratio of the conductive assistant having a particle diameter of 5 nm or more and less than 30 nm in a cross section of the electrode layer may be 0.05% or more and less than 4%, and the area ratio of the conductive assistant having a particle diameter of 20 nm or more and less than 130 nm may be 1% or more and less than 4%.

[0010] In the all-solid-state battery, a total area ratio of the conductive assistant in a cross section of the electrode layer may be 1.05% or more and less than 8%.

[0011] In the all-solid-state battery, the conductive assistant may be a carbon material.

[0012] In the all-solid-state battery, the carbon material may be a fibrous carbon material.

[0013] In the all-solid-state battery, the carbon material may be a carbon nanotube.

[0014] In the all-solid-state battery, the solid electrolyte layer may be an oxide.

[0015] In the all-solid-state battery, the solid electrolyte layer may be a phosphate-based oxide.

[0016] In the all-solid-state battery, the solid electrolyte layer and the electrode layer may be sintered bodies. Effect of the Invention

[0017] According to the present invention, it is possible to provide an all-solid-state battery that can realize good battery operation while keeping the ratio of a conductive assistant that does not contribute to capacity low. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a basic structure of an all-solid-state battery. [Diagram 2] FIG. [Diagram 3] FIG. 2 is a partial cross-sectional perspective view of a stacked-type all-solid-state battery in which a plurality of battery units are stacked. [Figure 4] FIG. 2 is a partial cross-sectional perspective view of a stacked-type all-solid-state battery in which a plurality of battery units are stacked. [Diagram 5] FIG. 2A is a diagram illustrating an example of the frequency distribution of particle diameters of a conductive assistant, and FIG. 2B is a diagram illustrating an example of the cumulative distribution. [Figure 6] FIG. 2A is a diagram illustrating an example of the frequency distribution of particle diameters of a conductive assistant, and FIG. 2B is a diagram illustrating an example of the cumulative distribution. [Figure 7] 1A and 1B are perspective views illustrating an example of a conductive additive, and FIG. 1C is a cross-sectional view illustrating a laminated positive electrode layer. [Figure 8] FIG. 1 is a diagram illustrating a flow of a method for producing an all-solid-state battery. [Figure 9] 1(a) and (b) are diagrams illustrating the lamination process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, an embodiment will be described with reference to the drawings.

[0020] (Embodiment) Fig. 1 is a schematic cross-sectional view showing a basic structure of an all-solid-state battery 100 according to an embodiment. As illustrated in Fig. 1, the all-solid-state battery 100 has a structure in which a solid electrolyte layer 30 is sandwiched between a positive electrode layer 10 and a negative electrode layer 20. For example, the positive electrode layer 10 is formed on a first main surface of the solid electrolyte layer 30, and the negative electrode layer 20 is formed on a second main surface of the solid electrolyte layer 30. The positive electrode layer 10, the negative electrode layer 20, and the solid electrolyte layer 30 are sintered bodies.

[0021] The solid electrolyte layer 30 is mainly composed of a solid electrolyte having ion conductivity. The solid electrolyte of the solid electrolyte layer 30 is, for example, an oxide-based solid electrolyte having lithium ion conductivity. The solid electrolyte is, for example, a phosphate-based solid electrolyte having a NASICON structure. The phosphate-based solid electrolyte having a NASICON structure has a high electrical conductivity and is stable in the air. The phosphate-based solid electrolyte is, for example, a phosphate containing lithium. The phosphate is not particularly limited, but examples thereof include a composite lithium phosphate salt with Ti (for example, LiTi2(PO4)3). Alternatively, Ti can be partially or completely replaced with a tetravalent transition metal such as Ge, Sn, Hf, or Zr. In order to increase the Li content, it may be partially replaced with a trivalent transition metal such as Al, Ga, In, Y, or La. More specifically, for example, Li 1+x Al x Ge 2-x (PO4)3 and Li 1+x Al x Zr 2-x (PO4)3, Li 1+x Al x Ti 2-x(PO4)3. For example, Li-Al-Ge-PO4-based material to which the same transition metal as that contained in the phosphate having an olivine crystal structure contained in the positive electrode layer 10 and the negative electrode layer 20 is added in advance is preferable. For example, when the positive electrode layer 10 and the negative electrode layer 20 contain a phosphate containing Co and Li, it is preferable that the solid electrolyte layer 30 contains a Li-Al-Ge-PO4-based material to which Co is added in advance. In this case, the effect of suppressing the elution of the transition metal contained in the electrode active material into the electrolyte can be obtained. When the positive electrode layer 10 and the negative electrode layer 20 contain a phosphate containing a transition element other than Co and Li, it is preferable that the solid electrolyte layer 30 contains a Li-Al-Ge-PO4-based material to which the transition metal is added in advance.

[0022] As illustrated in FIG. 2, the positive electrode layer 10 has a structure in which an electrode active material 11, a solid electrolyte 12, a conductive assistant 13, and the like are dispersed. The negative electrode layer 20 has a structure in which an electrode active material 21, a solid electrolyte 22, a conductive assistant 23, and the like are dispersed. The positive electrode layer 10 includes the electrode active material 11, and the negative electrode layer 20 includes the electrode active material 21, so that the all-solid-state battery 100 can be used as a secondary battery. The positive electrode layer 10 includes the solid electrolyte 12, and the negative electrode layer 20 includes the solid electrolyte 22, so that the positive electrode layer 10 and the negative electrode layer 20 have ion conductivity. The positive electrode layer 10 includes the conductive assistant 13, and the negative electrode layer 20 includes the conductive assistant 23, so that the positive electrode layer 10 and the negative electrode layer 20 have conductivity.

[0023] The electrode active material 11 is, for example, an electrode active material having an olivine crystal structure. The electrode active material having an olivine crystal structure may also be contained in the negative electrode layer 20. An example of such an electrode active material is a phosphate containing a transition metal and lithium. The olivine crystal structure is a crystal that natural olivine has, and can be identified by X-ray diffraction.

[0024] A typical example of an electrode active material having an olivine crystal structure is LiCoPO4 containing Co and P. Phosphates in which the transition metal Co is substituted in this chemical formula can also be used. The ratio of Li and PO4 can vary depending on the valence. It is preferable to use Co, Mn, Fe, Ni, etc. as the transition metal. LiCo2P3O 10 , Li2CoP2O7, Li6Co5(P2O7)4, etc. can also be used.

[0025] For example, when an electrode active material having an olivine crystal structure is contained only in the positive electrode layer 10, the electrode active material acts as a positive electrode active material. When an electrode active material having an olivine crystal structure is also contained in the negative electrode layer 20, although the mechanism of action is not completely clear, the effect of increasing the discharge capacity and increasing the operating potential with discharge is exhibited, which is presumed to be based on the formation of a partial solid solution state with the negative electrode active material.

[0026] When both the positive electrode layer 10 and the negative electrode layer 20 contain an electrode active material having an olivine crystal structure, the electrode active materials preferably contain transition metals that may be the same or different from each other. "May be the same or different from each other" means that the electrode active materials contained in the positive electrode layer 10 and the negative electrode layer 20 may contain the same type of transition metal, or may contain different types of transition metals. The positive electrode layer 10 and the negative electrode layer 20 may contain only one type of transition metal, or may contain two or more types of transition metals. Preferably, the positive electrode layer 10 and the negative electrode layer 20 contain the same type of transition metal. More preferably, the electrode active materials contained in both electrodes have the same chemical composition. If the positive electrode layer 10 and the negative electrode layer 20 contain the same type of transition metal or contain an electrode active material of the same composition, the similarity of the compositions of the two internal electrode layers is increased, so that even if the terminals of the all-solid-state battery 100 are attached in the opposite direction, the battery can withstand practical use without malfunction depending on the application.

[0027] The negative electrode layer 20 functions as a negative electrode layer by including the electrode active material 21. By including the negative electrode active material in only one electrode, it becomes clear that the one electrode acts as a negative electrode and the other electrode acts as a positive electrode. However, both electrodes may include a material that is known as a negative electrode active material. For the negative electrode active material of the electrode, reference can be made to conventional techniques in secondary batteries as appropriate, and examples thereof include compounds such as titanium oxide, lithium titanium composite oxide, lithium titanium composite phosphate, carbon, and lithium vanadium phosphate.

[0028] The solid electrolyte 12 and the solid electrolyte 22 are not particularly limited as long as they are oxide-based solid electrolytes having ion conductivity. The solid electrolyte 12 and the solid electrolyte 22 are, for example, oxide-based solid electrolytes having lithium ion conductivity. The solid electrolyte is, for example, a phosphate-based solid electrolyte having a NASICON structure. The phosphate-based solid electrolyte is, for example, a phosphate containing lithium. The phosphate is not particularly limited, but examples thereof include a composite lithium phosphate salt with Ti (for example, LiTi2(PO4)3). Alternatively, Ti can be partially or completely replaced with a tetravalent transition metal such as Ge, Sn, Hf, or Zr. In addition, in order to increase the Li content, it may be partially replaced with a trivalent transition metal such as Al, Ga, In, Y, or La. More specifically, for example, Li 1+x Al x Ge 2-x (PO4)3 and Li 1+x Al x Zr 2-x (PO4)3, Li 1+x Al x Ti 2-x (PO4)3, etc. The solid electrolyte 12 and the solid electrolyte 22 may be, for example, the same as the main component solid electrolyte of the solid electrolyte layer 30. Alternatively, when the electrode active material contains Co and P, the solid electrolytes 12 and 22 preferably contain Co. Although the detailed mechanism is unclear, the inclusion of Co during co-firing tends to improve the oxidation resistance stability of the solid electrolyte, which makes it easier to ensure cycle stability.

[0029] The material of the conductive assistant 13, 23 is not particularly limited as long as it has conductivity, but as an example, a carbon material is used as the material of the conductive assistant 13, 23. A metal may be used as the material of the conductive assistant 13, 23. Examples of the metal of the conductive assistant include Pd, Ni, Cu, Fe, and alloys containing these.

[0030] 3 is a schematic cross-sectional view of a stacked type all-solid-state battery 100a in which a plurality of battery units are stacked. The all-solid-state battery 100a includes a stacked chip 60 having a substantially rectangular parallelepiped shape. In the stacked chip 60, a first external electrode 40a and a second external electrode 40b are provided so as to contact two side surfaces, which are two of the four surfaces other than the upper and lower surfaces at the ends in the stacking direction. The two side surfaces may be two adjacent side surfaces, or may be two side surfaces facing each other. In this embodiment, the first external electrode 40a and the second external electrode 40b are provided so as to contact two side surfaces facing each other (hereinafter referred to as two end surfaces).

[0031] In the following description, components having the same composition range, thickness range, and particle size distribution range as those of the all-solid-state battery 100 are denoted by the same reference numerals and detailed description thereof will be omitted.

[0032] In the all-solid-state battery 100a, a plurality of positive electrode layers 10 and a plurality of negative electrode layers 20 are alternately stacked with a solid electrolyte layer 30 interposed therebetween. The edges of the plurality of positive electrode layers 10 are exposed to the first end face of the stacked chip 60, but are not exposed to the second end face. The edges of the plurality of negative electrode layers 20 are exposed to the second end face of the stacked chip 60, but are not exposed to the first end face. As a result, the positive electrode layer 10 is electrically connected to the first external electrode 40a, and the negative electrode layer 20 is electrically connected to the second external electrode 40b. The solid electrolyte layer 30 extends from the first external electrode 40a to the second external electrode 40b. In this way, the all-solid-state battery 100a has a structure in which a plurality of battery units are stacked.

[0033] A cover layer 50 is laminated on the upper surface of the laminated structure of the positive electrode layer 10, the solid electrolyte layer 30, and the negative electrode layer 20 (in the example of FIG. 3, the upper surface of the uppermost positive electrode layer 10). In addition, a cover layer 50 is laminated on the lower surface of the laminated structure (in the example of FIG. 3, the lower surface of the lowermost positive electrode layer 10). The cover layer 50 is mainly composed of an inorganic material (e.g., Al2O3, ZrO2, TiO2, etc.) containing, for example, Al, Zr, Ti, etc. The cover layer 50 may contain the main component of the solid electrolyte layer 30 as a main component. The cover layer 50 is a sintered body.

[0034] The positive electrode layer 10 and the negative electrode layer 20 may each include a current collector layer. For example, as illustrated in FIG. 4, a first current collector layer 15 may be provided in the positive electrode layer 10. A second current collector layer 25 may be provided in the negative electrode layer 20. The first current collector layer 15 and the second current collector layer 25 are mainly composed of a conductive material. For example, metal, carbon, etc. may be used as the conductive material of the first current collector layer 15 and the second current collector layer 25. The current collection efficiency is improved by connecting the first current collector layer 15 to the first external electrode 40a and connecting the second current collector layer 25 to the second external electrode 40b.

[0035] As described above, the positive electrode layer 10 and the negative electrode layer 20 contain a conductive assistant from the viewpoint of electrical conductivity. For example, when a conductive assistant with a small particle size is used in the positive electrode layer 10 and the negative electrode layer 20, the electron conduction to each electrode active material is good, and good battery operation can be realized. However, if the particle size is too small, the conductive assistant may not be able to withstand heat during sintering. If a conductive assistant with a large particle size is used, the electronic conductivity of the entire electrode layer is high, and good battery characteristics can be obtained. However, if the particle size is too large, the ratio of the conductive assistant required to form an electronic conduction path for each electrode active material is high, and high capacity may not be realized.

[0036] Therefore, the all-solid-state batteries 100, 100a according to this embodiment have a configuration that can realize good battery operation while keeping the ratio of the conductive assistant that does not contribute to the capacity low.

[0037] In this embodiment, both conductive assistants with small particle diameters and conductive assistants with large particle diameters are used as the conductive assistants 13, 23. Specifically, as illustrated in FIG. 5(a), when the frequency distribution of particle diameters of the conductive assistant 13 in a cross section (e.g., a cross section including the stacking direction) of the positive electrode layer 10 is calculated, the two largest peaks appear in the range of 5 nm to 130 nm. Of these two peaks, the one with the smaller particle diameter is referred to as the first peak A, and the one with the larger particle diameter is referred to as the second peak B. In addition, as illustrated in FIG. 5(b), when the cumulative distribution of particle diameters is calculated, a point appears between the first peak A and the second peak B where the slope is 0.7 or less (% / nm).

[0038] For example, the examples in Figures 5(a) and 5(b) show a mixture of a conductive additive with an average particle size of 25 nm and a conductive additive with an average particle size of 45 nm, with a particle volume ratio of 27:1. In Figure 5(b), the slope of D40% to D80% in the vicinity of the first peak A is 4.59 (% / nm), which is greater than 0.7. The slope of D88% to D94% in the vicinity of the second peak B is 0.773 (% / nm), which is greater than 0.7. The slope of D83% to D88% between the first peak A and the second peak B is 0.676 (% / nm), which is less than 0.7.

[0039] The examples in Figures 6(a) and 6(b) show a mixture of a conductive additive with an average particle size of 25 nm and a conductive additive with an average particle size of 55 nm, with a particle volume ratio of 8:1. In Figure 6(b), the slope of D33% to D76% in the vicinity of the first peak A is 4.26 (% / nm), which is greater than 0.7. The slope of D82% to D95% in the vicinity of the second peak B is 0.930 (% / nm), which is greater than 0.7. The slope of D76% to D82% between the first peak A and the second peak B is 0.606 (% / nm), which is less than 0.7.

[0040] In addition, when the frequency distribution of the particle diameters of the conductive assistant 23 in the cross section (e.g., the cross section including the stacking direction) of the negative electrode layer 20 is calculated, the first peak A and the second peak B appear in the range of 5 nm to 130 nm. In addition, when the cumulative distribution of the particle diameters is calculated, a point appears between the first peak A and the second peak B where the gradient is 0.7 (% / nm).

[0041] According to this configuration, the conductive assistant with a small particle size can take charge of the electronic conduction of each electrode active material. As a result, good battery characteristics can be obtained. In addition, since the first peak A appears in the range of 5 nm to 130 nm, the particle size of the conductive assistant with a small particle size does not become too small. As a result, it becomes possible to withstand heat during sintering. On the other hand, the conductive assistant with a large particle size takes charge of the electronic conduction of the entire electrode layer, and good battery characteristics can be obtained. In addition, since the second peak B appears in the range of 5 nm to 130 nm, the particle size of the conductive assistant with a large particle size does not become too large. As a result, the conductive assistant ratio can be suppressed. From the above, good battery operation can be achieved while keeping the ratio of the conductive assistant that does not contribute to the capacity low.

[0042] In addition, if the frequency of the first peak A and the second peak B in the frequency distribution is low, the effect of the conductive assistant with a small particle size and the effect of the conductive assistant with a large particle size may not be fully obtained. Therefore, it is preferable to set a lower limit for the frequency of the first peak A and the second peak B. For example, the frequency of the first peak A and the second peak B is preferably 3% or more, more preferably 4% or more, and even more preferably 5% or more.

[0043] Furthermore, in the frequency distribution, if the difference between the particle size of the first peak A and the particle size of the second peak B is small, the effect of the conductive assistant with a small particle size and the effect of the conductive assistant with a large particle size may not be fully obtained. Therefore, it is preferable to set a lower limit for the difference between the particle size of the first peak A and the particle size of the second peak B. For example, the difference between the particle size of the first peak A and the particle size of the second peak B is preferably 10 nm or more, more preferably 15 nm or more, and even more preferably 20 nm or more.

[0044] In the positive electrode layer 10, if the amount of the conductive assistant 13 is small, sufficient conductivity may not be obtained, and if the amount of the conductive assistant 13 is large, sufficient capacity may not be obtained. Therefore, it is preferable to set a lower limit and an upper limit for the amount of the conductive assistant 13. For example, in the cross section of the positive electrode layer 10, it is preferable that the area ratio of the conductive assistant 13 having a particle diameter of 5 nm or more and less than 30 nm is 0.05% or more and less than 4%, and the area ratio of the conductive assistant 13 having a particle diameter of 20 nm or more and less than 130 nm is 1% or more and less than 4%. In addition, it is preferable that the total area ratio of the conductive assistant 13 in the cross section of the positive electrode layer 10 is 1.05% or more and less than 8%.

[0045] In the negative electrode layer 20, if the amount of the conductive assistant 23 is small, sufficient conductivity may not be obtained, and if the amount of the conductive assistant 23 is large, sufficient capacity may not be obtained. Therefore, it is preferable to set a lower limit and an upper limit for the amount of the conductive assistant 23. For example, in the cross section of the negative electrode layer 20, it is preferable that the area ratio of the conductive assistant 23 having a particle diameter of 5 nm or more and less than 30 nm is 0.05% or more and less than 4%, and the area ratio of the conductive assistant 23 having a particle diameter of 20 nm or more and less than 130 nm is 1% or more and less than 4%. In addition, it is preferable that the total area ratio of the conductive assistant 23 in the cross section of the negative electrode layer 20 is 1.05% or more and less than 8%.

[0046] The material of the conductive assistant 13, 23 is not particularly limited as long as it is a material having conductivity, but is preferably a carbon material. Since the carbon material is soft, it is possible to suppress the breakthrough of the solid electrolyte layer 30. For example, it is preferable to use a fibrous carbon material as the conductive assistant 13, 23. In this case, since the width of the conductive assistant 13, 23 is small, it is possible to secure an ion conduction path between the positive electrode layer 10 and the negative electrode layer 20 compared to the case where plate-shaped carbon is used. It is preferable to use carbon nanotubes or the like as the conductive assistant 13, 23. Since the carbon nanotubes have a hollow fiber shape and are soft, it is possible to suppress the breakthrough of the solid electrolyte layer 30.

[0047] In addition, from the viewpoint of ensuring the content of the electrode active material, the area ratio of the electrode active material 11 in the positive electrode layer 10 and the area ratio of the electrode active material 21 in the negative electrode layer 20 in the laminate cross section are preferably 30% or more, and more preferably 40% or more.

[0048] On the other hand, from the viewpoint of ensuring the solid electrolyte content, the area ratio of the electrode active material 11 in the positive electrode layer 10 and the area ratio of the electrode active material 21 in the negative electrode layer 20 are preferably 75% or less, and more preferably 70% or less.

[0049] From the viewpoint of preventing breakthrough by the conductive assistants 13, 23, etc., the thickness of the solid electrolyte layer 30 is preferably 6 μm or more, and more preferably 7 μm or more.

[0050] On the other hand, from the viewpoint of ensuring rate characteristics, the thickness of the solid electrolyte layer 30 is preferably 19 μm or less, and more preferably 18 μm or less.

[0051] Fig. 7(a) is a perspective view illustrating the conductive assistant 13, 23. As illustrated in Fig. 7(a), the conductive assistant 13, 23 has, for example, a fibrous shape and has a long diameter and a short diameter. The aspect ratio (long diameter:short diameter), which is the ratio of the long diameter to the short diameter, is preferably 100:1 to 3000:1, more preferably 125:1 to 1000:1, and further preferably 150:1 to 500:1.

[0052] In order to ensure a sufficient conductive distance, the overall length of the conductive assistants 13, 23 is preferably 1.5 μm or more, more preferably 2.5 μm or more, and even more preferably 5 μm or more.

[0053] The conductive assistants 13, 23 do not need to extend linearly in the positive electrode layer 10 and the negative electrode layer 20, and may be curved as shown in FIG. 7(b). When carbon nanotubes are used, the hollow portion may be a gap or may be filled with other materials. When a fibrous carbon material is used, it is preferable that the carbon material has a particle diameter of 5 nm or more in order to achieve sufficient thermal stability.

[0054] FIG. 7(c) is a diagram illustrating a cross section of the positive electrode layer 10. The cross section of the stack can be exposed by grinding the all-solid-state battery 100, 100a. The cross section of the stack can be observed by a scanning electron microscope (SEM) or the like. The particle diameter of the conductive assistant 13 can be obtained by measuring the shortest diameter passing through the center of gravity of the cross section. The average diameter of the conductive assistant 23 in the negative electrode layer 20 can also be measured by a similar procedure. The area ratio of the conductive assistant 13 can be measured by, for example, using image analysis software (ImageJ Fiji: Schneider, CA, Rasband, WS, Elieiri, KW "NIH Image to ImageJ: 25 years of image analysis." Nature Methods 9, 671-675, 2012) to obtain the ratio of the cross-sectional area of ​​the conductive assistant 13 to the total area of ​​the SEM image. The area ratio of the conductive assistant 23 in the negative electrode layer 20 can also be measured by a similar procedure.

[0055] The thickness of the solid electrolyte layer 30 can be measured by observing a cross section of the stack of the all-solid-state batteries 100, 100a with an SEM, measuring the thickness at ten different points in one layer, and deriving the average value.

[0056] Next, a description will be given of a method for manufacturing the all-solid-state battery 100a illustrated in Fig. 3. Fig. 8 is a diagram illustrating a flow of the method for manufacturing the all-solid-state battery 100a.

[0057] (Process for producing raw powder for solid electrolyte layer) First, a raw material powder for the solid electrolyte layer constituting the above-mentioned solid electrolyte layer 30 is prepared. For example, raw materials, additives, etc. are mixed, and a solid-phase synthesis method or the like is used to prepare raw material powder for an oxide-based solid electrolyte. The obtained raw material powder can be dry-milled to adjust to a desired average particle size. For example, a planetary ball mill using 5 mmφ ZrO2 balls is used to adjust to a desired average particle size.

[0058] (Cover layer raw powder preparation process) First, the raw material powder of the ceramics constituting the above-mentioned cover layer 50 is prepared. For example, the raw material powder for the cover layer can be prepared by mixing the raw materials, additives, etc., and using a solid-phase synthesis method, etc. The obtained raw material powder can be adjusted to a desired average particle size by dry pulverizing. For example, the desired average particle size is adjusted using a planetary ball mill using 5 mmφ ZrO2 balls.

[0059] (Electrode layer paste preparation process) Next, the internal electrode pastes for producing the above-mentioned positive electrode layer 10 and negative electrode layer 20 are separately prepared. For example, the electrode active material and the solid electrolyte material are highly dispersed using a bead mill or the like to produce a ceramic paste consisting only of ceramic particles. The conductive assistants 13 and 23 are mixed into this ceramic paste. Since the fibrous carbon is entangled, a dispersion process is performed using a solvent for the paste and an appropriate dispersant using an ultrasonic homogenizer or a wet jet mill. The ceramic paste, the dispersion of the conductive assistants 13 and 23, and the binder are mixed to produce the electrode layer paste.

[0060] The sintering aid of the internal electrode paste contains one or more glass components such as Li-BO based compounds, Li-Si-O based compounds, Li-CO based compounds, Li-SO based compounds, and Li-PO based compounds.

[0061] (External electrode paste manufacturing process) Next, an external electrode paste for producing the above-mentioned first external electrode 40a and second external electrode 40b is prepared. For example, the external electrode paste can be obtained by uniformly dispersing a conductive material, a glass frit, a binder, a plasticizer, etc. in water or an organic solvent.

[0062] (Solid electrolyte green sheet manufacturing process) The raw material powder for the solid electrolyte layer is uniformly dispersed in an aqueous or organic solvent together with a binder, a dispersant, a plasticizer, etc., and wet-pulverized to obtain a solid electrolyte slurry having a desired average particle size. At this time, a bead mill, a wet jet mill, various kneaders, a high-pressure homogenizer, etc. can be used, and it is preferable to use a bead mill from the viewpoint of simultaneously adjusting the particle size distribution and dispersing. A binder is added to the obtained solid electrolyte slurry to obtain a solid electrolyte paste. The obtained solid electrolyte paste is coated to produce a solid electrolyte green sheet 51. The coating method is not particularly limited, and a slot die method, a reverse coat method, a gravure coat method, a bar coat method, a doctor blade method, etc. can be used. The particle size distribution after wet-pulverization can be measured, for example, using a laser diffraction measurement device using a laser diffraction scattering method.

[0063] (Lamination process) As illustrated in FIG. 9(a), the internal electrode paste 52 is printed on one side of the solid electrolyte green sheet 51. In the area on the solid electrolyte green sheet 51 where the internal electrode paste 52 is not printed, the reverse pattern 53 is printed. The reverse pattern 53 can be the same as the solid electrolyte green sheet 51. A plurality of printed solid electrolyte green sheets 51 are alternately shifted and stacked. As illustrated in FIG. 9(b), a laminate is obtained by pressing the cover sheets 54 from above and below in the stacking direction. In this case, a laminate having a substantially rectangular parallelepiped shape is obtained so that the internal electrode paste 52 for the positive electrode layer 10 is exposed on one end surface of the laminate and the internal electrode paste 52 for the negative electrode layer 20 is exposed on the other end surface of the laminate. The cover sheet 54 can be formed by applying the raw material powder for the cover layer in the same manner as in the solid electrolyte green sheet preparation process. The cover sheet 54 is formed to be thicker than the solid electrolyte green sheet 51. It may be made thicker during coating, or it may be made thicker by stacking multiple coated sheets.

[0064] Next, the external electrode paste 55 is applied to each of the two end faces by a dipping method or the like, and then dried. This provides a molded body for forming the all-solid-state battery 100a.

[0065] (Firing process) Next, the obtained laminate is fired. The firing conditions are not particularly limited, and may be in an oxidizing or non-oxidizing atmosphere, and the maximum temperature is preferably 400°C to 1000°C, more preferably 500°C to 900°C, etc. In order to sufficiently remove the binder before the maximum temperature is reached, a step of maintaining the temperature in an oxidizing atmosphere at a temperature lower than the maximum temperature may be provided. In order to reduce process costs, it is desirable to fire at as low a temperature as possible. After firing, a reoxidation treatment may be performed. Through the above steps, an all-solid-state battery 100a is produced.

[0066] In addition, a collector layer can be formed in the positive electrode layer 10 and the negative electrode layer 20 by sequentially laminating an internal electrode paste, a collector paste containing a conductive material, and an internal electrode paste. EXAMPLES

[0067] (Examples 1 to 5) The electrode active material and the solid electrolyte were highly dispersed in a bead mill to prepare a ceramic paste consisting of only ceramic particles. Carbon nanotubes were used as a conductive assistant. Since the carbon nanotubes are entangled, they were dispersed using a solvent for the paste and an appropriate dispersant with an ultrasonic homogenizer or a wet jet mill. The conditions of the dispersion treatment were adjusted so that the aspect ratio of the fiber diameter of the carbon nanotubes was 100:1 to 1000:1. The ceramic paste, the dispersion liquid of the carbon nanotubes, and the binder were mixed to prepare an electrode paste. Then, the electrode paste was printed and laminated on the solid electrolyte layer, and fired to form an external electrode to prepare an all-solid-state battery. In each of Examples 1 to 5, the amount and particle size of the conductive assistant were adjusted.

[0068] The cross section of the sintered battery was polished by ion milling and observed with an SEM to determine the particle size and area ratio of each conductive assistant contained in the electrode layer. For the particle size, a frequency distribution and a cumulative distribution were calculated. In the frequency distribution of Examples 1 to 5, the two largest peaks, the first peak A and the second peak B, appeared in the range of 5 nm or more and 130 nm or less. In addition, in the cumulative distribution, a point appeared between the first peak A and the second peak B where the slope was 0.7 or less (% / nm).

[0069] In Example 1, the particle size of the first peak A was 25 nm, the frequency of the first peak was 24%, the particle size of the second peak B was 45 nm, the frequency of the second peak was 5.4%, and the minimum slope between the first peak A and the second peak B was 0.67. In Example 2, the particle size of the first peak A was 25 nm, the frequency of the first peak was 22%, the particle size of the second peak B was 55 nm, the frequency of the second peak was 5.7%, and the minimum slope between the first peak A and the second peak B was 0.61. In Example 3, the particle size of the first peak A was 25 nm, the frequency of the first peak was 8.7%, the particle size of the second peak B was 65 nm, the frequency of the second peak was 9.9%, and the minimum slope between the first peak A and the second peak B was 0.49. In Example 4, the particle size of the first peak A was 20 nm, the frequency of the first peak was 5.0%, the particle size of the second peak B was 66 nm, the frequency of the second peak was 7.5%, and the minimum slope between the first peak A and the second peak B was 0.53. In Example 5, the particle size of the first peak A was 25 nm, the frequency of the first peak was 22%, the particle size of the second peak B was 55 nm, the frequency of the second peak was 5.7%, and the minimum slope between the first peak A and the second peak B was 0.61.

[0070] In Example 1, the area ratio of the conductive assistant having a particle diameter of 5 nm or more and less than 30 nm was 3.5%, and the area ratio of the conductive assistant having a particle diameter of 20 nm or more and less than 130 nm was 1.0%. In Example 2, the area ratio of the conductive assistant having a particle diameter of 5 nm or more and less than 30 nm was 3.5%, and the area ratio of the conductive assistant having a particle diameter of 20 nm or more and less than 130 nm was 3.5%. In Example 3, the area ratio of the conductive assistant having a particle diameter of 5 nm or more and less than 30 nm was 0.2%, and the area ratio of the conductive assistant having a particle diameter of 20 nm or more and less than 130 nm was 3.0%. In Example 4, the area ratio of the conductive assistant having a particle diameter of 5 nm or more and less than 30 nm was 0.05%, and the area ratio of the conductive assistant having a particle diameter of 20 nm or more and less than 130 nm was 1.0%. In Example 5, the area ratio of the conductive assistant having a particle size of 5 nm or more and less than 30 nm was 5.0%, and the area ratio of the conductive assistant having a particle size of 20 nm or more and less than 130 nm was 5.0%.

[0071] Comparative Example 1 In Comparative Example 1, only one peak 1 appeared in the range of 5 nm or more and 130 nm or less in the frequency distribution of the particle diameter of the conductive assistant. The area ratio of the conductive assistant having a particle diameter of 5 nm or more and less than 30 nm was 3.0%, and the area ratio of the conductive assistant having a particle diameter of 20 nm or more and less than 130 nm was 0%. The other conditions were the same as in Example 1.

[0072] Comparative Example 2 In Comparative Example 2, in the frequency distribution of the particle diameter of the conductive assistant, only one peak 1 appeared in the range of 5 nm or more and 130 nm or less. The area ratio of the conductive assistant having a particle diameter of 5 nm or more and less than 30 nm was 0%, and the area ratio of the conductive assistant having a particle diameter of 20 nm or more and less than 130 nm was 3.0%. The other conditions were the same as in Example 1.

[0073] (Evaluation of battery characteristics) Battery characteristics were evaluated for each of Examples 1 to 5 and Comparative Examples 1 and 2. The battery characteristics were evaluated by CC charge / discharge measurement at 25°C (charge current 0.2C-discharge current 0.2C or charge current 1C-discharge current 1C, upper cut voltage 3.6V, lower cut voltage 1.5V). The rate characteristics were calculated by determining the ratio of the 1C discharge capacity when the 0.2C discharge capacity was 100%, and the ratio was judged as very good "◯" when it was 70% or more, good "△" when it was 60% or more, and poor "×" when it was less than 60%. The capacity values ​​were compared at 0.2C discharge capacity. The ratio of the discharge capacity value of each battery when the discharge capacity of Example 2 was 100% was calculated, and the ratio was judged as very good "◯" when it was 90% or more, good "△" when it was 80% or more, and poor "×" when it was less than 80%.

[0074] (Cycle characteristics) In addition, the cycle characteristics were examined for each of Examples 1 to 5 and Comparative Examples 1 and 2. Specifically, charging and discharging were performed at 1C at 25°C in the voltage range of 3.6V to 1.5V, and the discharge capacity after 100 cycles was evaluated as "Good" if it was 80% or more of the initial discharge capacity, "Average" if it was 60% or more, and "Poor" if it was 60% or less.

[0075] The results are shown in Table 1. In Examples 1 to 5, none of the rate characteristics, capacity, and cycle characteristics were judged to be poor "x". This is believed to be because the frequency distribution of the particle diameter of the conductive assistant agent shows the two largest peaks, the first peak A and the second peak B, in the range of 5 nm to 130 nm, and the cumulative distribution of the particle diameter shows a point where the slope between the first peak A and the second peak B is 0.7 or less (% / nm). In Comparative Example 1, the rate characteristics were judged to be poor "x". This is believed to be because a conductive assistant agent with a relatively large particle diameter was not included, and the conductivity of the entire electrode layer was reduced. In Comparative Example 2, the capacity and cycle characteristics were judged to be poor "x". This is believed to be because a conductive assistant agent with a relatively small particle diameter was not included, and the conductive path of each electrode active material was insufficient. [Table 1]

[0076] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to such specific embodiments, and various modifications and variations are possible within the scope of the gist of the present invention described in the claims. [Explanation of symbols]

[0077] 10 Positive electrode layer 11 Electrode active material 12 Solid electrolyte 13 Conductive additives 15 First current collector layer 20 Negative electrode layer 21 Electrode active material 22 Solid electrolyte 23 Conductive additives 25 Second collector layer 30 Solid electrolyte layer 40a First external electrode 40b 2nd external electrode 50 Cover Layer 51 Solid electrolyte green sheet 52 Internal electrode paste 53 Reverse pattern 54 Cover Sheet 55 External electrode paste 60 Stacked Chips 70 side margin 100,100a solid state battery

Claims

1. A solid electrolyte layer; and an electrode layer provided on each of the main surfaces of the solid electrolyte layer and containing an electrode active material and a conductive assistant, an all-solid-state battery, in which a frequency distribution of particle diameters of the conductive additive in a cross section of the electrode layer has two largest peaks, a first peak and a second peak, in a range of 5 nm or more and 130 nm or less, and in which a cumulative distribution of the particle diameters has a point between the first peak and the second peak, the slope of which is 0.7 (% / nm) or less.

2. The all-solid-state battery according to claim 1 , wherein in the frequency distribution, the first peak and the second peak have a frequency of 5% or more.

3. The all-solid-state battery according to claim 1 , wherein a difference between a particle size of the first peak and a particle size of the second peak is 20 nm or more.

4. 2. The all-solid-state battery according to claim 1, wherein in a cross section of the electrode layer, an area ratio of the conductive assistant having a particle diameter of 5 nm or more and less than 30 nm is 0.05% or more and less than 4%, and an area ratio of the conductive assistant having a particle diameter of 20 nm or more and less than 130 nm is 1% or more and less than 4%.

5. The all-solid-state battery according to claim 1 , wherein a total area ratio of the conductive assistant in a cross section of the electrode layer is 1.05% or more and less than 8%.

6. The all-solid-state battery according to claim 1 , wherein the conductive assistant is a carbon material.

7. The all-solid-state battery according to claim 6 , wherein the carbon material is a fibrous carbon material.

8. The all-solid-state battery according to claim 6 , wherein the carbon material is a carbon nanotube.

9. The all-solid-state battery according to claim 1 , wherein the solid electrolyte layer is an oxide.

10. The all-solid-state battery according to claim 1 , wherein the solid electrolyte layer is a phosphate-based oxide.

11. The all-solid-state battery according to claim 1 , wherein the solid electrolyte layer and the electrode layer are sintered bodies.

Citation Information

Patent Citations

  • All-solid battery and method for manufacturing the same

    JP2021034202A

  • All-solid-state battery, green laminate for all-solid-state battery, and method for producing all-solid-state battery

    WO2014042083A1